Comparing Selected Life-History Traits of Black Soldier Fly (Diptera: Stratiomyidae) Larvae Produced in Industrial and Bench-Top-Sized Containers. Issue 5 (22nd October 2020) - Yang, Fangchun; Tomberlin, Jeffery K
Abstract: As global food demand is increasing along with human population growth, there is a greater need for alternative protein sources. Insect protein, especially the larvae of the black soldier fly, Hermetia illucens (L.) (Diptera: Stratiomyidae), has become a key approach for solving this issue in part due to its ability to convert organic waste into insect biomass with minimal resource (e.g., land, water) requirements. However, most information utilized to develop industrial production of this species is reliant on data generated from laboratory-scaled studies. Unfortunately, scaling these data to an industrial level potentially is not linear resulting in over, or under, estimating production. In this study, we compared selected life-history traits of larval black soldier fly produced at benchtop (e.g., 1 liter container with 614 larvae) and industrial scales (e.g., 29.5 liter container inoculated with 10, 000 larvae). Larvae were provided a single feeding (2 g/larva) in each treatment. Significant differences in the mean larval weight (24.7%), survivorship (−28.2%), and biomass conversion (−2.7%) were determined between benchtop and industrial treatments. These results indicate larval number and the associated container size are important factors to consider when designing a black soldier fly factory. Furthermore, caution should be taken when applying data from laboratory studies to industrial scale production systems as the values potentially are not linear.